Physiological determinants of the internesting interval in sea turtles: a novel 'water-limitation' hypothesis. (5th June 2019) - Price, Edwin R.; Sotherland, Paul R.; Wallace, Bryan P.; Spotila, James R.; Dzialowski, Edward M.
Abstract : The internesting interval separates successive clutches of sea turtle eggs, and its duration varies both among and within species. Here, we review the potential physiological limits to this interval, and develop the hypothesis that desalination capacity limits the internesting interval owing to the requirement for water deposition in eggs. Sea turtles deposit 1–4 kg of water per clutch in egg albumen; for most species, this represents about 2% of adult body mass. We calculate how quickly turtles can recover this water by estimating maximal salt excretion rates, metabolic water production and urinary losses. From this water balance perspective, the 'water-limitation' hypothesis is plausible for green turtles but not for leatherbacks. Some plasma biochemistry studies indicate dehydration in sea turtles during the nesting season, although this is not a universal finding and these data have rarely been collected during the internesting interval itself. There is mixed support for a trade-off between clutch size and the length of the interval. We conclude that the 'water-limitation' hypothesis is plausible for most sea turtle species, but requires direct experimentation.